Speculations about the New Lifestyle Privacy Needs in Domestic Space for Post-Capitalist Families - Husaini, Janin Mohammad Rafiq (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2021)
Throughout history, transformations in social, political, economic, and health situations have influenced the reformations in family structures that follow the changes in work positions of women and men, and which determine each era’s expected gender roles. Accordingly, this qualitative exploratory study has examined the issue of gendered privacy within family houses throughout the twentieth-century and onwards, in order to trace the marks of social changes in family structures and the embedded gender roles that were reflected upon the spatial arrangement of functions within houses. The main motivation to conduct this study was to provoke a discussion and to open new lines of thoughts about home, by speculating about the “Post-capitalist” family house for this time. A house that might ease the coming life challenges following the expected transformation of the economic system as a consequence of the current health crisis situation (COVID-19). To test the hypothesis that the traditionally gendered privacy/spatial arrangement of functions within family houses that prioritized “masculinity” have changed throughout time into a more democratic manner. A documentary survey was used together with a case study analysis of detached house plans from the twentieth-century and beyond in the U.S.A. The results revealed that the traditional “masculine-dominance” in the public zones was only in the first half of the century, then from the 1950s and onwards, slight changes have started to appear. These results have encouraged the speculative discussion about the new “Post capitalist” family household. A significant reformation of the family structure is expected to begin with the new domestic masculinities/femininities. Perhaps, the new “work-from-home” lifestyle is demanding more privacy between adults by having bigger and multiple-use master bedrooms that are partially-segregated, an additional work/study shared room or two separated rooms (depending on the house’s size), a multiple-use kitchen, bigger terraces/outdoor-spaces, etc.

ÖZ: Tarih boyunca, sosyal, politik, ekonomik ve sağlık durumlarındaki dönüşümler, her dönemin beklenen cinsiyet rollerini belirleyen, kadın ve erkeklerin çalışma pozisyonlarındaki değişiklikleri izleyen aile yapılarındaki reformları etkilemiştir. Bu çalışma, aile yapılarındaki sosyal değişimlerin izlerinin işlevlerin mekansal düzenlemesine yansıyan cinsiyet rollerini izlemek için yirminci yüzyıl boyunca ve sonrasında aile evlerinde cinsiyetlendirilmiş mahremiyet konusunu incelemiştir. Bu çalışmayı yürütmenin ana motivasyonu, “Post-kapitalist” aile evi hakkında spekülasyon yaparak tartışmaya yol açmak ve yeni düşüncelere yol açmaktır. Mevcut sağlık krizi durumunun (COVID-19) bir sonucu olarak ekonomik sistemin beklenen dönüşümünün ardından gelecek yaşam zorluklarını hafifletebilecek bir ev ve kamusal alanlarda “erkekliğe” öncelik veren aile evlerindeki işlevlerin geleneksel olarak cinsiyetlendirilmiş mahremiyet / mekansal düzenlemesinin zamanla daha demokratik bir şekilde değiştiği hipotezini test etmek. ABD'de yirminci yüzyıl ve sonrasına ait müstakil ev planlarının bir vaka analizi ile birlikte bir belgesel anket kullanıldı. Sonuçlar, kamusal alanlardaki geleneksel "erkeksi egemenliğin" sadece yüzyılın ilk yarısında olduğunu ortaya koydu. 1950'lerden itibaren küçük değişiklikler görülmeye başlandı. Bu sonuçlar, yeni “Kapitalizm Sonrası” aile hanesi hakkındaki spekülatif tartışmayı teşvik etti. Yeni aile içi erkek / kadın aile yapısındaki önemli bir reformun başlaması bekleniyor. Belki de yeni “evde kal” durumu, kısmen ayrılmış daha büyük ve çok kullanımlı ana yatak odaları, ek bir çalışma odası veya iki ayrı oda (evin büyüklüğüne bağlı olarak) ile yetişkinler arasında daha fazla mahremiyet talep ediyor. ), fonksiyonel mutfaklar, daha büyük teraslar / dış mekanlar vb.
Master of Science in Interior Architecture. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Architecture, Dept. of Interior Architecture, 2021. Supervisor: Assoc. Prof. Dr. Afet Coşkun
Keywords: Interior Architecture; Domestic Architecture; Gender roles; Privacy; Post-capitalism; Family house; Spatial arrangement; Domestic interior space